Regional Tourism Development Planning: A Structured Literature Review - Zainul Rahman; Salahudin Salahudin (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
This study aims at categorizing the themes and concepts that become problems in the study of regional tourism development. Various problems regarding related themes in several countries were then collaborated and used as references for the development of regional tourism in Indonesia in the future. This study was a structured literature review with the main data source obtained through the SCOPUS database. The SCOPUS database was considered very relevant and comprehensive to be used as a reference in preparing discussions on related themes. This study revealed several aspects that influenced the development of regional tourism in several countries so that it could be a reference to be applied in Indonesia. The aspects are: First, a well-integrated collaboration. Second, strong political will from the government. Third, the presence or active participation of the local community. Fourth, planning was carried out in a systematic and integrated manner. Finally, the fifth is the subject involved as policy makers. The limitations of this study were the lack of comprehensive comparisons reviewed in each cluster. It was based on the limitations of the data found by the authors, especially those that were only contained in the SCOPUS database. Through these existing limitations, it is expected that further study can enrich references from other databases for the progress of the study. Thus the discussion of related themes can be a detailed study and very useful in influencing regional tourism development policies in Indonesia in the future.